Effects of cannabis on congenital limb anomalies in 14 European nations: A geospatiotemporal and causal inferential study. Issue 1 (5th July 2022) - Reece, Albert Stuart; Hulse, Gary Kenneth
Abstract: Cannabinoid exposure is increasing in some European nations. Europe therefore provides an interesting test environment for the recently reported link between cannabis exposure and congenital limb anomaly (CLA) rates (CLARs). Exponential genotoxic dose–response relationships make this investigation both intriguing and imperative. Annual CLAR in 14 nations were from Epidemiological Surveillance of Congenital Anomalies. Drug use rates were from European Monitoring Centre for Drugs and Drug Dependency. Median household income was from the World Bank. E -values provide a quantitative measure of robustness of results to confounding by extraneous covariates. Inverse probability weighting is an important technique for equalizing exposures across countries and removing sources of bias. Rates of CLA, hip dysplasia and the whole group of limb anomalies were higher in countries with increasing daily cannabis use ( P  = 1.81 × 10 −16, 0.0005 and 2.53 × 10 −6, respectively). In additive inverse-probability-weighted panel models, the limb reduction-resin Δ9-tetrahydrocannabinol (THC) concentration E -value estimate was 519.93 [95% lower bound (mEV) 49.56], order Resin > Herb ≫ Tobacco > Alcohol. Elevations were noted in 86% E -value estimates and 70.2% of mEVs from 57 E -value pairs from inverse-probability-weighted panel models and from spatial models. As judged by the mEV the degree of association with metrics of cannabis exposure was hip dysplasia > polydactyly > syndactyly > limb anomalies > limb reductions with median E -value estimates from 3.40 × 10 65 to 7.06 and median mEVs from 6.14 × 10 33 to 3.41. Daily cannabis use interpolated was a more powerful metric of cannabis exposure than herb or resin THC exposure. Data indicate that metrics of cannabis exposure are closely linked with CLAR and satisfy epidemiological criteria for causality. Along with Hawaii and the USA, Europe now forms the third international population in which this causal link has been demonstrated. Cannabis as a predictor of limb anomalies was more potent than tobacco or alcohol. Cannabinoid access should be restricted to protect public health and the community genome/epigenome transgenerationally.